MEDIATING EFFECT OF CUSTOMER SATISFACTION IN THE RELATIONSHIP BETWEEN PERCEIVED USEFULNESS, ENJOYMENT, AND PRICE ON WILLINGNESS TO RE-SUBSCRIBE (EMPIRICAL STUDY AMONG NETFLIX USERS) - Vera, Vera Gitta Fernanda B1024171019 (Jurnal Manajemen Update, 2021)
AbstractThe purpose of this research is to analyze the Impact of Perceived Usefulness, Enjoyment, Price, and Customer Satisfaction on Willingness to Re-subscribe as well as the mediating role of Customer Satisfaction. As the internet users keep on developing it offers many business opportunities to companies that run platforms turning web-users into subscribers. Since the pandemic of Covid-19 hit Indonesia watching movies at home became a high trend which affects the increase in the numbers of VoD (Video on Demand) platform users. But, even though some VoD providers experienced an increase in users, the penetration of users considered to be slow due to the slow user adoption. From this point, the VoD industry needs to make the customer satisfied and willing to re-subscribe to their businesses. This Research was started in January and finished in March. This research was done in Pontianak area with a sample of 150 participants. In this research, the data analysis method used is Structural Equation Model Partial Least Square (SEMPLS) method. The result of this research shows that all of the hypotheses are accepted.  Keywords: Perceived Usefulness, Perceived Enjoyment, Perceived Price, Customer Satisfaction, Willingness to Re-subscribe.BIBLIOGRAPHYAren, S., Güzel, M., Alpkan, L., & Kabadayı, E. (2013). Factors Affecting Repurchase Intention to Shop at the Same Website. International Strategic Management ConferenceAt: RigaVolume: 9.Baskara, I. A., & Sukaadmadja, I. G. (2016). Pengaruh Online Trust dan Perceived Enjoyment terhadap Online Shopping Satisfaction dan Repurchase Intention Lazada Indonesia. E-Jurnal Manajemen Unud, Vol. 5, No. 11, 7214-7244.Bhattacherjee, A. (2001). Understanding Information System Continuance: An Expectation Confirmation Model. MIS Quarterly, Vol.25 No.3.Cheng, S.-Y., Tsai, M.-T., Cheng, N. C., & Chen, K.-S. (2012). Predicting Intention to Purchase on Group Buying Website in Taiwan. Online Information Review, 36 (5), 698-712.Chin, W. (1998). The Partial Least Squares Approach to Structural Equation Modeling. USA: Erlbaum.D.Davis, F. (1989). Perceived Usefulness, Perceived Ease of Use, and User Acceptance of Information Technology. MIS Quarterly, 23.Dah-Kwe, L., Li-Chun, H., & Wen-Hai, C. (2015). Understanding Broadband Television Users’ Continuance Intention to Use. Industrial Management & Data Systems, Vol. 115 Iss 2 pp, 35.Daud, A., Farida, N., Andriyansah, & Razak, M. (2018). Impact of Customer Trust Toward Loyalty: The Mediating Role of Perceived Usefulness and Satisfaction. Journal of Business and Retail Management Research (JBRMR), Vol. 13 Issue 2.Davis, F., Bagozzi, R., & Warshaw, P. (1992). Extrinsic and Intrinsic Motivation to Use Computer in the Workplace. Journal of Applied and Social Psychology, 22(14):1111-1132.Devaraj, S., Fan, M., & Kohli, R. (2002). Antecedents of B2C Channel Satisfaction and Preference: Validating e-Commerce Metrics. Information Systems Research, 19.Dong, X., Chang, Y., Wang, Y., & Yan, J. (2017). Understanding Usage of Internet of Things (IOT) Systems in China: Cognitive Experience and Affect Experience as Moderator. Information Technology & People, Vol. 30 No. 1, pp. 117-138.Ellya, N., & Dian, A. (2008). Hubungan Kepuasan Pasien Bayar dengan Minat Kunjungan Ulang di Puskesmas Wisma Jaya Kota Bekasi. Jurnal Kesehatan Masyarakat, Vol. 12, No. 1.Garson, G. (2016). Partial Least Square: Regression & Structural Equation Models. USA: Statistical Associates Publishing.Ghozali, I. (2021). Partail Least Squares Konsep, Teknik, dan Aplikasi Menggunakan Program SmartPLS 3.2.9 Untuk Penelitian Empiris. Semarang: Badan Penerbit Universitas Diponegoro.Hair, J., Hult, G., Ringle, C., & Sarstedt, M. (2014). Primer on Partial Least Squares Structural Equation Modeling (PLS-SEM). Thousand Oaks: Sage.Hanseler, J., Ringle, C. M., & Sarstedt, M. (2012). Using Partial Least Squares Path Modeling in International Advertising Research: Basic Concepts and Recent Issues. Pp. 252-276 in Okzaki, S., ed. Handbook of Partial Least Squares: Concepts, Methods and Applications in Marketing and Related Fields. Berlin: Springer.Hendar, Sudarti, K., & Rhemananda, H. (2020). Online Customers Satisfaction on Repurchase Intention: Role of Mobile Shopping Perceived Customer. In: Barolli L., Poniszewska-Maranda A., Enokido T. (eds) Complex, Intelligent and Software Intensive Systems. CISIS 2020. Advances in Intelligent Systems and Computing, vol 1194. Springer, Cham.Huang, Y.-T., Lee, K.-W., & Chan, W.-Y. (2011). An Empirical Study of Consumer’s Repurchase Intention of Tablet PC. The 6th International Conference on Computer Science & Education, 6.Jiang, P., & Rosenbloom, B. (2005). Customer Intention to Return Online: Price Perception, Attribute-level Performance, and Satisfaction Unfolding Over Time. European Journal of Marketing 39:150-174.Jung, Y., Mira, B. P., & Patton, S. W. (2009). Consumer Adoption of Mobile TV: Examining Psychological Flow. Computers in Human Behavior 25.Kim, C., D.Galliers, R., Shin, N., Ryoo, J.-h., & Jongheon, K. (2012). Factors influencing Internet shopping value and customer repurchase intention. Electronic Commerce Research and Applications.Kim, D., Ferrin, D., & Rao, H. (2009). Trust and Satisfaction, Two Stepping Stones for Successful E-Commerce Relationships: A Longitudinal Exploration. Information Systems Research, 38.Kotler, P., & Keller, K. (2009). Manajemen Pemasaran, Edisi Tigabelas, Jilid Satu. Jakarta: Erlangga.Kuo, C.-W., & Tang, M.-L. (2013). Relationships among Service Quality, Corporate Image,Customer Satisfaction, and Behavioral Intention for the Elderly in High Speed Rail Services. Journal of Advanced Transportation, 47(5), 512 525.Lin, C.-Y., Fang, K., & Tu, C.-C. (2010). Predicting Consumer Repurchase Intentions to Shop Online. Journal of Computers 5(10):1527-1533.Liu, C.-H., & Tingko, L. (2016). Service Quality and Price Perception of Service: Influence on Word-of-Mouth and Revisit Intention. Journal of Air Transport Management 52:42-54.Park, S., Kang, S.-u., & Zo, H. (2016). Analysis of influencing factors on the IPTV subscription: Focused on the moderation role of user perceived video quality. Information Technology & People.Praveena, K., & Thomas, S. (2013). Continuance Intention to Use Facebook: A Study of Perceived Enjoyment and TAM. Bonfring International Journal of Industrial Engineering and Management Science, Vol. 4, No. 1.Setyowati, E., & Wiyadi. (2016). Pengaruh Kualitas Pelayanan, Harga dan Citra Merek terhadap Loyalitas Pelanggan dengan Kepuasan Pelanggan Sebagai Variabel Pemediasi. Jurnal Ekonomi Manajemen Sumber Daya, Vol. 18, No. 2.Srivastava, D., & Sharma, N. (2013). Service Quality, Corporate Brand Image, and Switching Behavior: The Mediating Role of Customer Satisfaction and Repurchase Intention. Services Marketing Quarterly, 34(4), 274 291.Suhaily, L., & Soelasih, Y. (2017). What Effects Repurchase Intention of Online Shopping. International Business Research; Vol. 10, No. 12; 2017, 10.Tuan, N. (2012). Effects of Service Quality and Price Fairness on Student Satisfaction . International Journal of Business and Social Science, 3(9), 132-150.Utami, C. W. (2010). Manajemen Ritel (Strategi dan Implementasi Operasional Bisnis Ritel Modern di Indonesia). Jakarta: Salemba Empat.Venkatesh, V. (2000). Determinants of Perceived Ease of Use: Integrating Control,Intrinsic Motivation, and Emotion into the Technology Acceptance Model. Information Systems Research, 11(4), 342–365.Wen, C., R.Prybutok, V., & Xu, C. (2011). An Integrated Model for Customer Online Repurchase Intention. Journal of Computer Information System, 10.Zeithaml , V., Bitner , M., & Gremler, D. (2006). Service Marketing. New York, NY.: Mc Graw-Hill.